Digital Marketing Ketan Susu & Kopi Sagara dalam Meningkatkan Brand Awareness - Dede Andri Saputra; Iva Fikrani Deslia (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research aims to analyze the digital marketing strategy implemented by Ketan Susu & Kopi Sagara in increasing brand awareness through social media platforms. The approach used is the SOSTAC model (Situation, Objectives, Strategy, Tactics, Action, Control) as an analytical framework. Data was obtained through interviews with business owners, observation of social media content, as well as documentation of insights and netizen interactions. The results showed that Ketan Susu & Kopi Sagara relies more on promotion through third-party accounts such as @info_nongkrongjogja than personal business accounts. This strategy is considered effective because it succeeds in reaching a wider target market of young people through visual reels content, communicative captions, the right upload time, and the use of contemporary language styles. The strategy evaluation showed that this digital promotion resulted in high engagement, increased customer visits, and positive testimonials through comments and user generated content (UGC). Thus, collaborative digital marketing strategies have proven effective in increasing brand awareness of culinary MSMEs in the digital era.